In Search of Confianza: A Qualitative Analysis of Salvadoran Parents’ Experiences in U.S. Urban Schools - Colón, Ingrid; James, Marlon; Chowdhury, Mahjabin; Rector-Aranda, Amy; Burgess Monroy, Miguel (International Journal of Multicultural Education, 2020)
This qualitative study of six recently arrived parents from El Salvador who have been in the U.S. for no longer than a year explores their experiences in U.S. schools and offers recommendations for actualizing an ethos of humanitarianism in schools. In particular, the study addresses the perspectives of recently arrived Salvadoran parents about their children’s education and how can schools effectively collaborate with parents to support the emotional, social, cultural, and educational needs of their children. The study drew on testimonios to learn about Salvadoran parents’ perspectives about their children’s education to improve the services their children need in schools.